LAJU SINTASAN DAN PERTUMBUHAN NILA MERAH (Oreochromis sp.) STRAIN CANGKRINGAN DAN TETUANYA PADA FASE PENDEDERAN - , BRISKHA BAKHRUDIN H ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research on rearing of fry red nile, (Oreochromis sp.) strain Cangkringan compare with the parental strain was conducted to determine survival rate and growth rate. This experience with designed to completely randomized design (CRD) with three replications each treatment. Fish fry again of 30 days were stocked 50 fry/m2 in each treatment. The treatment consists of Cangkringan strain and three parental strains : Philippines, Nifi, and Citralada strain. The rearing was conducted for 2 months with feeding 2 times a day in the morning and afternoon with ransume the eat 5% biomass/days. Fish sampling was done every 2 weeks as much as 15% of biomass to measure length and weight of the fish as well as water quality. Parameters those canculated were absolue growth, specific growth rate, survival rate, feed conversion ratio, and water quality. The results showed that there were significant differences (P<0.05) on survival rate and growth rate between strain Cangkringan and parental strain. Cangkringan strain has absulete growth, of weight and length also spesifik growth rate higher but survival rate lower than Nifi and Philippines.